2010
DOI: 10.1103/physrevlett.104.178104
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pilus Motors Cooperate for Persistent Bacterial Movement in Two Dimensions

Abstract: In various bacterial species surface motility is mediated by cycles of type IV pilus motor elongation, adhesion, and retraction, but it is unclear whether bacterial movement follows a random walk. Here we show that the correlation time of persistent movement in Neisseria gonorrhoeae increases with the number of pili. The unbinding force of individual pili from the surface F=10 pN was considerably lower than the stalling force F>100 pN, suggesting that density, force, and adhesive properties of the pilus motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

15
121
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(138 citation statements)
references
References 15 publications
15
121
2
Order By: Relevance
“…This finding was more notable in the magnified view (Fig. 5E, Inset), proving that the twitching motility was activated randomly with an apparent diffusion coefficient of 1.2 μm 2 /s, which is good agreement with the scaling behavior of the motility in other bacteria (26,27). The start point of the parabolic line indicates the phase transition to directed twitching motility as a result of the negative phototaxis.…”
Section: Resultssupporting
confidence: 72%
“…This finding was more notable in the magnified view (Fig. 5E, Inset), proving that the twitching motility was activated randomly with an apparent diffusion coefficient of 1.2 μm 2 /s, which is good agreement with the scaling behavior of the motility in other bacteria (26,27). The start point of the parabolic line indicates the phase transition to directed twitching motility as a result of the negative phototaxis.…”
Section: Resultssupporting
confidence: 72%
“…1a). No biochemical mechanism coordinating their retraction is known, yet the quantitative analysis of bacterial trajectories provides clear evidence for the cooperation of multiple pili 15 . These observations suggested that the coordination of multiple pilus motors may be mediated mechanically via a tug-of-war of pilus motors pulling in different directions 15 .…”
mentioning
confidence: 99%
“…No biochemical mechanism coordinating their retraction is known, yet the quantitative analysis of bacterial trajectories provides clear evidence for the cooperation of multiple pili 15 . These observations suggested that the coordination of multiple pilus motors may be mediated mechanically via a tug-of-war of pilus motors pulling in different directions 15 . Furthermore, diplococci (pairs of bacteria) were observed to align and meander in micro-topographic grooves, consistent with a tug-of-war between pili on either side of the bacterium 33 .…”
mentioning
confidence: 99%
See 2 more Smart Citations